Design and characterization of functional interfaces for fundamental studies of nitro-polycyclic aromatic hydrocarbon chemistry - Murphy, Deirdre M. (Trinity College (Dublin, Ireland). School of Chemistry, 2014)
Nitro-polycyclic hydrocarbons (nPAHs) are a class of highly mutagenic compounds whose reactions and fates in the atmosphere have a tremendous effect on atmospheric chemistry. In the troposphere, the photodegradation of nPAHs occurs as a heterogeneous reaction on carbonaceous particles. In this work we aimed to design and characterize functional nPAH/carbon interfaces for fundamental studies of nitro-polycyclic aromatic hydrocarbon chemistry.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin